Statement from Kuupik Kleist at the NRF Open Assembly 2011 - Kuupik, Kleist (Arctic Portal, 2011)
The Premier of Greenland, Mr. Kuupik Kleist, attended the 6th NRF Open Assembly in Hveragerði Iceland in September 2011. In the opening session he spoke these words in his statement. Please click on the link above to see the video.